Two new copper(II) binuclear complexes with 2-[(E)-(pyridine-2yl-hydrazono)methyl]phenol: Molecular structures, quantum chemical calculations, cryomagnetic properties and catalytic activity. (15th September 2020) - Patel, R.N.; Patel, S.K.; Kumhar, D.; Patel, Nirmala; Patel, A.K.; Jadeja, R.N.; Patel, Neetu; Butcher, R.J.; Cortijo, M.; Herrero, S.
Graphical abstract: The copper(II) binuclear complexes [Cu2 (µ-ClO4 )(L)2 (H2 O)2 ](ClO4 )·H2 O (1) and [Cu2 (µ-pyrazine)(L)2 ](ClO4 )2 (2) with 2-[(E)-(pyridine-2yl-hydrazono)methyl]phenol (HL), were synthesized and characterized using various physicochemical techniques. The molecular structures of both binuclear complexes were evaluated by single-crystal X-ray analysis. Analysis of the supramolecular synthons and their effect on crystal packing is conferred in the context of crystal engineering. Highlights: Synthesized and characterization of two copper(II) hydrazone complexes. Copper complexes are binuclear having distorted square pyramidal and distorted square planar geometry respectively. Complexes have shown a strong antiferromagnetic interaction. Both complexes catalyzed the dismutation of superoxide ( O 2 ∙ - ). Complexes have shown HOMO-LUMO energy gap. Abstract: The Schiff base is synthesized by the reaction of 2-hydrazinopyridine and salicylaldehyde. The copper(II) binuclear complexes [Cu2 (µ-ClO4 )(L)2 (H2 O)2 ](ClO4 )·H2 O(1) and [Cu2 (µ-pyrazine)(L)2 ](ClO4 )2 (2) with 2-[(E)-(pyridine-2yl-hydrazono)methyl]phenol (HL), were synthesized and characterized using various physicochemical techniques. The molecular structures of both binuclear complexes were evaluated by single-crystal X-ray analysis. Analysis of the supramolecular synthons and their effect on crystal packing is conferred in the context of crystal engineering. The electron paramagnetic spectra are reported as well. The electrochemical behavior of both complexes was explored using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. The electronic and spectral properties are described by quantum chemical calculations (TD and DFT).The cryomagnetic investigation (2–300 K) reveal antiferromagnetic exchange coupling between two copper(II) centres of different strength: J CuCu = −21.6 and J CuCu = -6.8 cm −1 for 1 and 2, respectively. The strong antiferromagnetic coupling between the copper centers found in 1 could be explained not only by magnetic exchange through hydrogen bonds but also through the π-π stacking of the Schiff base ligands. Both binuclear complexes exhibit catalytic activity toward the dismutation of superoxide anion at physiological pH. Although the activity in both complexes is lower than the native enzyme, they have potential as antioxidant SOD model for pharmaceutical applications.